Highly diverse population of Picornaviridae and other members of the Picornavirales, in Cameroonian fruit bats - Yinda, Claude Kwe (BMC Genomics, 2017)
BACKGROUND: The order Picornavirales represents a diverse group of positive-stranded RNA viruses with small non-enveloped icosahedral virions. Recently, bats have been identified as an important reservoir of several highly pathogenic human viruses. Since many members of the Picornaviridae family cause a wide range of diseases in humans and animals, this study aimed to characterize members of the order Picornavirales in fruit bat populations located in the Southwest region of Cameroon. These bat populations are frequently in close contact with humans due to hunting, selling and eating practices, which provides ample opportunity for interspecies transmissions. RESULTS: Fecal samples from 87 fruit bats (Eidolon helvum and Epomophorus gambianus), were combined into 25 pools and analyzed using viral metagenomics. In total, Picornavirales reads were found in 19 pools, and (near) complete genomes of 11 picorna-like viruses were obtained from 7 of these pools. The picorna-like viruses possessed varied genomic organizations (monocistronic or dicistronic), and arrangements of gene cassettes. Some of the viruses belonged to established families, including the Picornaviridae, whereas others clustered distantly from known viruses and most likely represent novel genera and families. Phylogenetic and nucleotide composition analyses suggested that mammals were the likely host species of bat sapelovirus, bat kunsagivirus and bat crohivirus, whereas the remaining viruses (named bat iflavirus, bat posalivirus, bat fisalivirus, bat cripavirus, bat felisavirus, bat dicibavirus and bat badiciviruses 1 and 2) were most likely diet-derived. CONCLUSION: The existence of a vast genetic variability of picorna-like viruses in fruit bats may increase the probability of spillover infections to humans especially when humans and bats have direct contact as the case in this study site. However, further screening for these viruses in humans will fully indicate their zoonotic potential. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-017-3632-7) contains supplementary material, which is available to authorized users.